2019
DOI: 10.3390/jcm8030298
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Older Patients (≥60 years) with New-Onset Idiopathic Nephrotic Syndrome Receiving Immunosuppressive Regimen: A Multicentre Study of 116 Patients

Abstract: Because of its rarity, renal presentation and outcomes of idiopathic nephrotic syndrome (INS; minimal changes disease or focal and segmental glomerulosclerosis) has poorly been described in elderly patients, precluding an individualized therapy procedure. Whether immunosuppressive regimens formerly designed in children and young adults are safe and efficient in elderly remains elusive. In a large multicentric retrospective study that included 116 patients with INS and onset ≥ 60 years of age, we showed that cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Colliou et al. 44 showed that 85% of patients developing INS after the age of 60 years have a complete or partial renal response on corticosteroids and/or immunosuppressive regimens. In the POLARIS (Prospective Observational Survey on the Long-Term Effects of LDL Apheresis on Drug-Resistant Nephrotic Syndrome) study, Muso et al.…”
Section: Discussionmentioning
confidence: 99%
“…Colliou et al. 44 showed that 85% of patients developing INS after the age of 60 years have a complete or partial renal response on corticosteroids and/or immunosuppressive regimens. In the POLARIS (Prospective Observational Survey on the Long-Term Effects of LDL Apheresis on Drug-Resistant Nephrotic Syndrome) study, Muso et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study that included patients with an average age of 51.5 ± 20.1 years, the relapse frequency decreased significantly after rituximab treatment, from 0.83 (0.18, 1.92) to 0.00 (0.00, 0.71) times per year [28]. Another study involving elderly patients aged 60 or older with MCD or FSGS showed that rituximab-induced complete or partial remission in 18 out of 23 patients [29]. Despite the age difference in our study (median age 25.0, range 20.0–40.5), our results were consistent with these previous studies in which rituximab reduced relapse frequency and corticosteroid exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Even for minimal change disease, only 50% had entered complete remission by 6 months, much lower than that reported in the literature. [6][7][8] Given the nature of routine data, there are of course limitations to the study, although these have been addressed where possible. The major issues concern the very limited information about baseline comorbidities, and relatively small numbers, particularly for models of subgroups in which many estimates have wide confidence intervals.…”
Section: See Clinical Research On Page 449mentioning
confidence: 99%
“…Even for minimal change disease, only 50% had entered complete remission by 6 months, much lower than that reported in the literature. 6 , 7 , 8 …”
mentioning
confidence: 99%